EXAMINING FACTORS INFLUENCING BRAND LOYALTY TOWARDS FAST FASHION BRAND IN DHAKA, BANGLADESH - Labiba Nawar, Chowdhury Antara; Sirion Chaipoopirutana (AU Hybrid International Conference 2024 on " Entrepreneurship & Sustainability in the Digital Era" under the theme of "People Centric Knowledge in Intelligence World", 2021)
Today’s fashion market is highly competitive and the constant need to ‘refresh’ product ranges gives consumers endless options to choose from which is why brand loyalty plays an important role for business’s to retain their consumers. The purpose of this study is to examine factors influencing brand loyalty towards a fast fashion brand in Dhaka, Bangladesh. 400 respondents were applied in order to investigate the statistical treatment of the data. Data were collected by using survey questionnaires and both simple linear and multiple linear regression analysis were used to test the hypotheses. The results indicate that there is a relationship between each variable for brand loyalty. Among them, social media marketing in term of responsiveness has the strongest influence on value consciousness followed by brand consciousness. Also, brand personality has the strongest influence on brand loyalty followed by social media marketing and brand uniqueness. The findings of this research will be beneficial to not only Aarong but also for other fast fashion brands. It can support data which may help the fast fashion industry to modify and improve more effective and proficient marketing tools and business model based on the knowledge of the influences of the factors in this research in order to create brand loyalty and accomplish the ultimate goals of the organization.